How to realize digital transformation in satellite communication industry? -- Configuration analysis based on the technology-organization-environment framework - Wang, Liting; Zhang, Huajian; Jin, Liang; Wang, Quan; Shi, Lifeng; Duan, Kun; Liu, Peng; Han, Jie; Dong, Hao (Frontiers in Environmental Science, 2023)
Digital transformation is the key link of the prosperity and development of digital economy, and the successful digital transformation is the result of the synergy of multi-level factors. Based on the theoretical framework of "technology-organization-environment" (TOE), this paper takes 27 satellite communication enterprises as samples and uses fuzzy set qualitative comparative analysis method to explore the configuration effect of six antecedent conditions at the level of technology, organization and environment on digital transformation of satellite communication enterprises. The results show that a single antecedent condition does not constitute a necessary condition for digital transformation. There are four configuration paths for digital transformation of satellite communication industry, which are technology-organization-oriented, technology-organization-environment collaboration-oriented, technology-organization-oriented environment collaboration, and organization-environment-oriented. Under certain conditions, there is substitution effect between antecedents. The conclusion reveals the complex causes of the digital transformation of Chinese satellite communication enterprises, and can provide beneficial enlightenment for the digital transformation of satellite communication enterprises.